Annealing effect on the photoelectrochemical and photocatalytic performance of TiO2 nanorod arrays. Issue 81 (6th November 2017) - Xie, Zheng; Shuang, Shuang; Ma, Lingwei; Zhu, Fei; Liu, Xiangxuan; Zhang, Zhengjun
Abstract : The photoelectrochemical and photocatalytic properties of TiO2 nanorod arrays annealed in the air were investigated. Abstract : TiO2 nanorod arrays (NRAs) with 540 nm length and an amorphous porous structure, were fabricated by oblique angle deposition method. The as-prepared amorphous TiO2 NRAs transform gradually into anatase phase after annealing with a temperature higher than 350 °C, whereas the specific surface area decreases due to the better crystallinity. The intensity of hydroxyl groups increases with enhancing annealing temperature, then decreases above 450 °C. The photocatalytic and photo-conversion properties benefit from the high crystallinity of TiO2 NRAs and high density of hydroxyl groups on the surface. It shows that TiO2 NRAs annealed at 450 °C exhibit the highest photoconversion efficiency and maximum degradation rate of MO, which can be ascribed to the excellent crystallization and the optimum density of hydroxyl groups on the surface of TiO2 . The TiO2 NRAs with enhanced crystallinity and fine structures are very promising for photocatalyst materials for environmental protection.